The impact of cosmetic advertisements in television: a case study among students in Kolej Melati UiTM Shah Alam / Noraini Jamal - Jamal, Noraini (2017)
The purpose of this study is to study the impact of cosmetic advertisement in television among students in Kolej Melati. This research only involves female students and it is conducted at Kolej Melati,UiTM Shah Alam. The research applies Uses & Gratification Theory because it fit to the topic and relate to the variables. The researcher also use quantitative research as the methodology to conduct this study by use descriptive analysis which is the transformation ofraw data into a form so that it is easy to understand, interpret, to produce descriptive information. Besides that, the researcher distribute questionnaire to the 70 respondent that from variety of field of study. Statistical Package for the Social Science (SPSS) also helps the researcher to change the raw to significant data for this research.